From the Evaluator’s Perspective: A Functional Approach to Social Judgments - Bitektine, Alex; Gillespie, Nicole; Lange, Donald (Academy of Management Review, 2026)
To deepen understanding of social judgments of organizations, we build on work that has adopted the evaluator’s perspective to develop a comprehensive functional approach to social judgments. We identify a set of adaptive challenges faced by evaluators in their relationship with organizations and theorize how the judgments they make can help resolve those challenges. In doing so, we clarify how social judgments are rooted in comparisons between the organization’s properties and some social referent, and extend understanding of the interrelated nature and complementary role of diverse social judgments. We explain how social judgments—such as legitimacy, trustworthiness, reputation, status, and authenticity—form a robust system of interrelated judgments that allows evaluators to collect and triangulate multiple judgments of different types, using judgment inputs from three different sources: (1) first-hand inputs, based on the evaluator’s own observations and information about the organization; (2) borrowed inputs, based on judgments made by others; and (3) taken-for-granted judgment inputs acquired through the evaluator’s socialization and education. We conclude by suggesting ways to reorient research toward unduly neglected elements of social judgment theory through systematic examination of the functional utility that social judgments provide for evaluators.